2022
DOI: 10.1007/s13353-022-00707-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of glutathione S-transferase gene family in Musa acuminata L. AAA group and gaining an insight to their role in banana fruit development

Abstract: Glutathione S-transferases are a multifunctional protein superfamily that is involved in diverse plant functions such as defense mechanisms, signaling, stress response, secondary metabolism, plant growth and development. Although the banana whole genome sequence is available but the distribution of GST genes on banana chromosomes, their subcellular localization, gene structure, their evolutionary relation with each other, conserved motifs and their roles in banana are still unknown. A total of 50 full length G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The 37 CcGST genes were localized in nine Cajanus chromosomes. The pattern of the chromosomal distribution of CcGSTs was found in clusters in the proximal or distal end, as reported in wheat (Wang et al 2019b) and banana GSTs (Vaish et al 2022). It is reported that the origin of new members in a gene family is majorly due to gene duplication events and is a key factor in plant genome evolution [53].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The 37 CcGST genes were localized in nine Cajanus chromosomes. The pattern of the chromosomal distribution of CcGSTs was found in clusters in the proximal or distal end, as reported in wheat (Wang et al 2019b) and banana GSTs (Vaish et al 2022). It is reported that the origin of new members in a gene family is majorly due to gene duplication events and is a key factor in plant genome evolution [53].…”
Section: Discussionmentioning
confidence: 52%
“…The number of exon/intron was conserved among the classes such as two exons in tau, three exons in phi, six exons in DHAR, GHR, and EF1G, seven exons in theta class, ten exons in zeta, and eight exons in lambda. Multiple sequence alignment revealed the conservation of signature motifs in eight CcGST classes such as W(A/V)S(P/M) in tau, (E/Q)SR(A/K/G)I in phi, SQPS/C in theta, SSCS/A in zeta, CPF/YA in lambda, CPFC/S in DHAR, and CPWA in GHR (Vaish et al 2020;Vaish et al 2022;Wang et al 2019b). Phosphorylation is the most common post-translational modi cation in proteins that plays a major role in plant functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, its primary function is to catalyze the coupling of some electrophilic groups with the thiols of reduced glutathione, to change its hydrophobicity so that it can easily cross the cell membrane to the extracellular space after being decomposed, thus achieving detoxification [ 70 , 71 ]. According to previous genome-wide identification reports of the GST family, it has been found that it has functions related to oxidative stress responses to abiotic stress [ 17 , 72 , 73 , 74 , 75 ]. AtGSTF8 , AtGSTU19 , and AtGST1 relieved salt stress by maintaining redox homeostasis in A. thaliana roots [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cysteinyl and serinyl GST perform diverse functions; for example, the serinyl group is involved in the glutathionylation reactions, comprising coupling of glutathione to foreign substances, rendering them soluble and they are subsequently expelled from the plant cell. On the other hand, cysteinyl GST facilitates deglutathionylation reactions and also catalyzes the reduction of dehydroascorbate [32][33][34].…”
Section: Introductionmentioning
confidence: 99%